Electroencephalographic assessment of pneumatically powered penetrating and non-penetrating captive-bolt stunning of bulls - Gibson, Troy John; Octavio Oliveira, Steffan Edward [UNESP]; Dalla Costa, Filipe Antonio [UNESP]; Gregory, Neville George (Elsevier B.V., 2019)
The electroencephalographic (EEG) responses of 31 bulls (zebu crossbred cattle) stunned with either pneumatically powered Jarvis penetrating (PCB) or non-penetrating captive bolt (NPCB) was examined. Animals were organized into two treatment groups: PCB (n = 20); and NPCB (n = 11) stunning, both using airline pressures of 220 psi (1517 kPa). All bulls shot with PCB (n = 20/20) had patterns of EEG activity that were inconsistent with consciousness. Of the cattle shot with NPCB 82% (n = 9/11) showed waveforms suggesting complete unconsciousness. After stunning two NPCB bulls had periods of normal EEG activity and maintenance (Ptot, delta, theta, beta) or increased (alpha) spectral power compared to pre-treatment values, indicating incomplete concussion. The study showed that pneumatic PCB stunning was effective in rendering all bulls unconscious, while NPCB was less effective. This highlights the potential animal welfare risks associated with NPCB compared to PCB stunning of mature bulls in commercial abattoirs.
Keywords: Bulls; Cattle; Electroencephalogram (EEG); Non-penetrating; Penetrating; Pneumatic captive bolt stunning